NON-TRAUMATIC FRACTURES IN INDIVIDUALS WITH DIABETES - Fraser, Lisa-Ann (My University, 2011)
Background: Previous studies have found that diabetes is associated with increased risk of fracture; however, the risk of non-traumatic fracture (of any bone) specific to individuals with diabetes across the Canadian population has not been studied.
Methods: Ten years of data from the Canadian Multicenter Osteoporosis study was explored. Logistic regression models were used to study factors associated with a history of previous non-traumatic fracture at study baseline. Cox proportional hazards models were used to explore time-to-incident-fracture during the 10 years of study.
Results: All women and men ≥ 50 years were included in the analyses (n=7753). This included 508 individuals with NIDDM and 98 with IDDM. Mean age was 67 (±9) years and 72% were female. Individuals with diabetes were found to be more likely to have a history of fragility fracture then non-diabetic CaMos participants (odds ratio [OR] =1.21, 95% confidence interval [CI] 1.00,1.46; p=0.04), but were less likely to be treated with bisphosphonate therapy during the 10 year study (OR: 0.58; 95% CI 0.46,0.75; p<0.001). History of a stroke/TIA or hypertension were found to be associated with previous non-traumatic fracture amongst the diabetic population (OR: 1.51; 95% CI 1.20,1.91; p<0.001; and, OR: 1.16; 95% CI 1.04,1.29; p=0.01 respectively).
Conclusions: A treatment care gap exists amongst diabetics in Canada. Individuals with diabetes are at increased risk of non-traumatic fracture, but are less likely to be treated with bisphosphonate therapy. Clinicians can use specific fracture risk factors to identify which diabetics are at highest risk and target interventions accordingly.
Keywords: fracture; diabetes; osteoporosis; falls; bisphosphonate; hypertension; Medicine and Health Sciences; Medicine and Health Sciences